Aesthetic Paradigm of Balaghah: Study of Language Aestethic in The Qur’an - Rizky Anugrah; Nursaid Agil Almunawar; Muhammad Fauzan Hizbullah (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2026)
Language is one of the most important instruments in human life, serving not only as a means of communication but also as a medium for expressing beauty. In the Islamic intellectual tradition, the aesthetic dimension of language is extensively studied through the discipline of Balaghah. This discipline developed as a methodological framework for understanding how meaning is conveyed in a precise, effective, and aesthetically refined manner. This study aims to examine the aesthetic paradigm in Balaghah and to explain the principles that underlie its understanding of the beauty of the Qur’anic language.This research uses a library research method with a descriptive-qualitative approach. Data were collected from various classical and contemporary sources on Balaghah and analyzed using content analysis techniques. The findings show that the aesthetic paradigm regards linguistic beauty asan inseparable part of meaning.This beauty is manifested through the harmony between wording (lafaz) and meaning, the role of dzauq (linguistic intuition or sensitivity. Therefore, the aesthetic paradigm contributes significantly to understanding the miraculous nature of Qur’anic language and to the development of Balaghah studies in the contemporary academic context.